Validation of the Youth Efficacy/Empowerment Scale – Mental Health Finnish version - Sakellari E; Athanasopoulou C; Kokkonen P; Sourander A; Leino-Kilpi H (Greece, 2022)
Αdolescents face mental health problems and still their mental health needs are often neglected. Empowerment provides adolescents with the skills to impact their own lives and communities in general. The aim of the study is to examine the validity and reliability of the Finnish version of the Youth Efficacy/Empowerment Scale – Mental Health (YES-MH). Data was collected through an online questionnaire from pupils aged 12–17 years in Western Finland, comprised of the following instruments; the YES-MH, the Goodman’s the Strengths and Difficulties Questionnaire (SDQ), and the Warwick-Edinburgh Mental Wellbeing Scale. Exploratory factor analysis was carried out to evaluate construct validity and disclose underlying structures which yielded the following subscales: Self, Services, System. The internal consistency of subscales was analyzed with Cronbach’s α. Construct validity was further investigated by computing the Pearson’s correlations coefficients between the subscales. Furthermore, correlations with SDQ and mental well-being dimensions were explored as measures of convergent validity. In the final model all items the Youth Efficacy/ Empowerment Scale – Mental Health were entered into the factor analysis. All factor loadings were more than 0.40, ranging from 0.63 to 0.89. All the scales exceeded the minimum reliability standard of 0.70 and all corrected item-total correlations were high. All the YES-MH subscales were significantly and positively correlated each other with correlations coefficients ranging from medium to high. Correlations of Mental Well-being score with Self and Services subscales were significant. Moreover, Self subscale was significantly correlated with all SDQ dimensions. Services subscale was significantly correlated with Emotional symptoms and total SDQ score, while System subscale was significantly correlated with Conduct problems. The exploratory factor analysis showed a clear factor structure and the results suggest that the YES-MH is a reliable scale for assessing empowerment among young people. The YES-MH can be useful for health professionals not only as an assessment tool but also when they need to evaluate mental health interventions and examine empowerment as an outcome. However, further research can provide insights for the use of the scale in specific adolescent target groups and among different ethnic groups as well.